A compact tri‐band antenna at GPS and WLAN a/b/g for tablet computer with full metal housing. Issue 8 (1st August 2016) - Chen, P.; Tang, X. J.; Wang, H.; Sim, C. Y. D.; Yang, G. L.
ABSTRACT: A very small antenna for full metal housing (FMH) tablet that can provide GPS and WLAN 2.4/5.2/5.8 GHz operations is presented. This miniaturized antenna is formed by a loop strip of about 41 mm with its end terminal connected to the ground via an inductor, and its front section capacitively coupled to a feed strip. Except for the antenna self‐resonant modes (loop modes); two cavity modes are also involved to realize multi‐bands operation, which is a novel technique for antenna design in FMH devices. Here, the three loop modes are at 1.575 GHz, 5.2 GHz, 6 GHz, and the two cavity modes are at 2.45 GHz and 5.4 GHz. The measured efficiencies at 1.575, 2.45, and 5.5 GHz were 36%, 79%, and 78%, respectively. Because the loop strip is only 0.18λ and in meander line shape at GPS frequency, the planar dimension of proposed antenna can be reduced to 10 × 8 mm 2 . Therefore, the proposed antenna has very competitive size for applications in this operation environment. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:739–746, 2016.